Using Praat for EFL English Pronunciation Class: Defining the Errors of Question Tags Intonation - Larassati, Anisa; Setyaningsih, Nina; Suryaningtyas, Valentina Widya; Cahyono, Setyo Prasiyanto (Language Circle: Journal of Language and Literature, 2022)
Expecting students to be able to speak English with proper pronunciation and intonation like native speakers is not an easy thing. So far, teaching English at the school level has focused on mastering grammar without focusing on language pronunciation (Silalahi, 2016, p. 163). Students in English Department, Faculty of Humanities, Universitas Dian Nuswantoro are required to take English Pronunciation course in their first semester. Based on the researchers’ teaching experience, one of the most common pronunciation errors was found in the intonation for question tags. This research aims to investigate students’ question tag pronunciation errors by using Praat software. It also tries to get the students’ perspective on the use of Praat as a teaching and learning aid for English Pronunciation course. This research employed qualitative descriptive method and used Dehe and Bettina (2013) research on English question tags as the analytical framework. The results showed that errors commonly occur on the pronunciation of down tags, both in conversation and sentences (68% and 53%). Meanwhile, the up tags errors were relatively lower (43%). It is most probably because the students were influenced by the intonation of Bahasa Indonesia, where questions were pronounced with rising intonation. However, after the students were introduced to Praat, the errors decreased significantly i.e., 7% for down tag in conversation, 13% for down tag in sentences, and 3% for up tags. The questionnaire reveals that students gave positive evaluation on the use of Praat in the classroom as it helped them evaluate their own pronunciation.